Hepatocellular carcinoma with thoracic metastases presenting as hemothorax: A case report and literature review. Issue 22 (June 2018) - Yen, Chih-Wei; Hsu, Li-Sheng; Chen, Chien-Wei; Lin, Wei-Hsiu
Abstract: Rationale: Hemothorax caused by metastasis or direct invasion of hepatocellular carcinoma (HCC) in the chest is rare. We report a case of hemothorax caused by metastasis in the mediastinum and treated with transcatheter arterial embolization (TAE). Patient concerns: A 60-year-old woman with HCC was admitted to receive chemotherapy. Two days after admission, she complained of dyspnea, and a chest X-ray revealed right pleural effusion. Thoracentesis confirmed the diagnosis of hemothorax. Computed tomography (CT) angiography showed lung, pleural, and mediastinal metastases and contrast extravasation from the right lower mediastinal mass. Diagnoses: Hemothorax caused by spontaneous rupture of mediastinal metastasis of hepatocellular carcinoma. Interventions: During emergent angiography, contrast extravasation from the right T10 intercostal artery was observed and we performed embolization with lipiodol and gelatin sponge particles. After embolization, no active bleeding was observed. Outcomes: The patient died because of sepsis and multiple organ failure 22 days after admission. Lessons: We reviewed 21 cases of HCC with metastasis or direct invasion in the chest presenting hemothorax. The results revealed that male sex and right hemothorax were predominant in these cases. The average age of the patients was 61.24±10.82 years. The most common symptoms were dyspnea, chest wall pain, and shock. Thoracentesis can confirm the diagnosis, and CT angiography can help identify the location of contrast extravasation before TAE. The reported bleeding arteries were the intercostal, inferior phrenic, bronchial, hepatic, and superficial cervical arteries. TAE with embolic agents is a feasible treatment. The overall outcomes in these cases were poor.